Department Of Pre-University Education Of Pushkin State Russian Language Institute: Work Experience And Specifics Of Professionally Oriented Tutorials - Маркина, Наталья Алексеевна; Шурупова, Ирина Викторовна (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
In the article discussed is a matter of preparation of foreign citizens to entering Russian universities at programs of bachelors, specialists, masters and postgraduate. Targets and tasks of their education are defined at preparation course of Pushkin State Russian Language Institute is that for entering Russian universities, foreign students must obsess, except Russian language from the level В1, as well the system of specialized disciplines, actual for further education, so one of key moments in the activity of department of Pre-University Education is tutorial the foreigners their specialty language by their profile, and kit of tutorial materials fit to their speaking level.